Anthropogenic and lithogenic fluxes of atmospheric lead deposition over the past 3600 years from a peat bog, Changbai Mountains, China. (July 2019) - Guo, Bobo; Wang, Jing; Lin, Chunye; He, Mengchang; Ouyang, Wei
Abstract: Ombrotrophic peatlands are widely used to reconstruct atmospheric metal deposition histories. Here, we estimated the long-term atmospheric Pb deposition flux using ombrotrophic peatland data from the Changbai Mountains, northeast China. A peat profile of 320-cm depth was sampled and cut into 164 slices for measurement of Pb and other elements by ICP-MS and ICP-AES and radiometric dating by 210 Pb, 137 Cs and 14 C. Pb concentration in the peat ranged from 2.18 to 68.33 mg kg −1, while the atmospheric Pb deposition flux ranged from 0.12 to 12.49 mg m −2 a −1 . The Little Ice Age (cold and wet climate) led to low Pb concentration, Pb/Sc ratio, and Pb deposition flux (4.40 ± 0.70 mg kg −1, 2.04 ± 0.38, and 0.28 ± 0.09 mg m −2 a −1, respectively). On the other hand, intense volcanic eruptions resulted in high Pb concentration, Pb/Sc ratio, and P flux (54.48 ± 13.08 mg kg −1, 7.85 ± 2.09, and 8.15 ± 2.85 mg m −2 a −1, respectively). In addition, rapid economic development since the 1980s resulted in a gradual increase of anthropogenic Pb concentration from 1.54 mg kg −1 to 5.85 mg kg −1 ; thus, the anthropogenic Pb deposition flux (0.43 ± 0.21 mg m −2 a −1 ) was high during this period. In general, peat Pb concentration and atmospheric Pb deposition fluxes in this region have been affected by climate change, volcanic eruptions, and human activities. It was further demonstrated that atmospheric Pb emissions and deposition in China decreased since leaded gasoline was phased out in 2001. The results are critical to understand the geochemistry of Pb and to assess the effects of human activities on atmospheric Pb emissions and deposition in China. Highlights: We estimate long-term atmospheric Pb deposition flux using ombrotrophic peatlands. The effect of human activities, climate change, and volcanic eruptions is analyzed. Peat cores in NE China provide long-term records of atmospheric Pb deposition. Climate, volcanism, and economic growth influenced anthropogenic Pb concentration.